ANTIMALARIAL POTENTIAL OF NATURAL ROTENOID EXTRACTED FROM PLANT Clitoria fairchildiana: A STRATEGY IN MOLECULAR DOCKING - Barbosa Belarmino, Anthony; Sousa, Damião Sampaio de; Mendes, Francisco Rogênio Da Silva; Marinho, Gabrielle Silva (Revista Multidisciplinar do Nordeste Mineiro, 2024)
Malaria is an arbovirosis present in several regions in which febrile illness caused by the Plasmodium parasite is characterized, being considered an acute life-threatening disease and a notable threat to global health. It is noteworthy that the methods of prevention are based on synthetic insecticides which can aggravate symptoms in patients. Thus, the insertion of natural compounds can contribute and improve the development of new ones for arboviroses. In this context, the objective of the study is the development of new therapeutic systems through natural compounds against the etiologic agent that causes malaria, aiming at the popularization of new approaches through the use of natural compounds in the treatment of neglected diseases. The strategy was based on in silico model in molecular docking, that is, the formation of an energetic complex between protein (DBL3x domain of the Plasmodium falciparum VAR2CSA) with the ligands obtained from C. fairchildiana (6_deoxyclitoriacetal, 9_demethylclitoriacetal, 11_deoxyclitoriacetal, Cloriacetal, Stemonal, and Stemonone) considering energetic parameters, RMSD (Root Mean Square Deviation) and interactions between the ligands and amino acids of the protein (VAR2CSA). Therefore, the compounds from C. fairchildiana presented energy and RMSD values within the suggested parameters, however, all the ligands did not interact with the residues of the active site of the protein. However, we cannot rule out the possibility of inhibition by allosteric modulation of the enzyme. It is emphasized that the study consists of an initial stage for the therapeutic development against neglected diseases using mainly the compounds extracted from C. fairchildiana due to its wide dissemination in Brazil and ethnopharmacological potential and expansion in vitro and in vivo studies for further validation.